E-Commerce Logistics System Based on Discrete Dynamic Modeling Analysis - Meng, Gaofei (Frontiers in Energy Research, 2022)
The development of green logistics in a low-carbon environment is the only way for logistics enterprises to reduce operating costs, and also a strategic measure to strengthen the construction of ecological civilization. The development of green logistics in a low-carbon environment should reduce environmental pollution as much as possible, avoid energy waste and strive to achieve energy conservation and emission reduction. With the advent of the era of big data, the e-commerce industry has ushered in a period of rapid development. Online shopping has pushed the development of the e-commerce industry to the peak. Taking the express logistics industry as an example, with the prosperity of online shopping, the scale of express logistics is becoming larger and larger. However, due to the passive development of the logistics industry because of increasing online shopping trend, the perfection of its own logistics system is far lower than its development speed. This leads to many problems in the logistics system, which is gradually exposed in the process of express service. In the environment of generally high logistics costs in China, the logistics problems make the upstream enterprises that rely on the express business to connect the downstream consumers invest a lot of costs every year to make up for the package damage and loss caused by logistics, resulting in a lot of asset losses, which seriously hinders the development of the overall economy. Therefore, based on this scenario, this paper improves the traditional bat algorithm based on discrete dynamic analysis algorithm.